Carbon-ion beam irradiation kills X-ray-resistant p53-null cancer cells by inducing mitotic catastrophe. - Napapat Amornwichet; Takahiro Oike; Atsushi Shibata; Hideaki Ogiwara; Naoto Tsuchiya; Motohiro Yamauchi; Yuka Saitoh; Ryota Sekine; Mayu Isono; Yukari Yoshida; Tatsuya Ohno; Takashi Kohno; et al. (PLoS ONE, 2014)
Background and purpose To understand the mechanisms involved in the strong killing effect of carbon-ion beam irradiation on cancer cells with TP53 tumor suppressor gene deficiencies. Materials and methods DNA damage responses after carbon-ion beam or X-ray irradiation in isogenic HCT116 colorectal cancer cell lines with and without TP53 (p53+/+ and p53-/-, respectively) were analyzed as follows: cell survival by clonogenic assay, cell death modes by morphologic observation of DAPI-stained nuclei, DNA double-strand breaks (DSBs) by immunostaining of phosphorylated H2AX (γH2AX), and cell cycle by flow cytometry and immunostaining of Ser10-phosphorylated histone H3. Results The p53-/- cells were more resistant than the p53+/+ cells to X-ray irradiation, while the sensitivities of the p53+/+ and p53-/- cells to carbon-ion beam irradiation were comparable. X-ray and carbon-ion beam irradiations predominantly induced apoptosis of the p53+/+ cells but not the p53-/- cells. In the p53-/- cells, carbon-ion beam irradiation, but not X-ray irradiation, markedly induced mitotic catastrophe that was associated with premature mitotic entry with harboring long-retained DSBs at 24 h post-irradiation. Conclusions Efficient induction of mitotic catastrophe in apoptosis-resistant p53-deficient cells implies a strong cancer cell-killing effect of carbon-ion beam irradiation that is independent of the p53 status, suggesting its biological advantage over X-ray treatment.